Factors Affecting the Implementation of Developmental Care in the Care of Premature Babies in NICU Nurses: A Systematic Review - CH.R. Yeni Suryandari; Yuni Sufyanti Arief; Sri Utami (Pediomaternal Nursing Journal, 2021)
Introduction: Developmental care-based preterm infant care management that aims to protect the neurological system and reduce adverse effects has developed over the last few decades. The study aimed to explore the factors that influence the implementation of developmental care among NICU nurses.Methods: The study was systematically identified by searching an electronic database using keywords "preterm infant" AND "developmental care" AND "nursing care" AND "NICU" and consisted of 2130 articles from Scopus, Science Direct, goggle scholar, ProQuest, and PubMed. Data sources were limited to articles published from 2015 to 2020 and those published in English. Thirteen studies were included in this systematic review. The inclusion criteria were nurses caring for preterm infants at the NICU, a cross-sectional descriptive study of quantitative or qualitative research.Results: Thirteen articles indicated that the developmental care implementation among NICU nurses was influenced by positive, perceptions knowledge, attitudes of developmental care. Professional skills are the most substantial impact on developmental care implementation to improve nurses' nursing development and increase the competence of individual nurses.Conclusion: Positive perceptions about organizational support and developmental care are needed. The training care program also benefits to nurses by increase self-confidence in implementing developmental care for premature babies.